2021
DOI: 10.3390/app11083691
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Oak Chips and Oak Barrel Ageing on Volatile Profile in Chardonnay Wine of Romania

Abstract: The influence of the addition of oak chips and barrel ageing on basic wine parameters and volatile compounds of Chardonnay wines has been studied. Chardonnay wines were obtained by the traditional wine-making process. Oak chips (4 g/L—non-toasted and light toasted) were added at the final stage of the winemaking process for ageing 1, 2 and 3 months, respectively. Also, the control wine was aged in non-toasted barrels for the same period of time. Following Liquid-liquid extraction-gas chromatography-mass spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Beverages 2023, 9, x FOR PEER REVIEW 12 wines have been reported [9][10][11]. For example, Koussissi et al [9] reported a higher centration of furfural and cis-oak-lactone in a red wine from the Greek grape cultivar A iorghitiko that was aged with medium-roasted chips compared to another that had b matured with deep-roasted chips.…”
Section: Sensory Analysis Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Beverages 2023, 9, x FOR PEER REVIEW 12 wines have been reported [9][10][11]. For example, Koussissi et al [9] reported a higher centration of furfural and cis-oak-lactone in a red wine from the Greek grape cultivar A iorghitiko that was aged with medium-roasted chips compared to another that had b matured with deep-roasted chips.…”
Section: Sensory Analysis Resultsmentioning
confidence: 99%
“…As previously described, the addition of wood chips provided the rosé wine with several sensory descriptors associated with wood aging. However, it would be interesting to carry out a more complete investigation in which different factors, such as number of chips, level of toasting, contact time of chips with wine, and even chips shape, were involved, since different effects on the physicochemical, sensory, and volatile profile of wines have been reported [9][10][11]. For example, Koussissi et al [9] reported a higher concentration of furfural and cis-oak-lactone in a red wine from the Greek grape cultivar Aghiorghitiko that was aged with medium-roasted chips compared to another that had been matured with deep-roasted chips.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was believed that this procedure lowered their quality due to the masking of the original fruit and floral notes found in white wines. Esters, alcohols, and terpenes are responsible for these specific floral and fresh notes of white wines [ 64 , 65 ]. Therefore, white wines need a special aging procedure to avoid the roasted and bitter aromas of furan compounds derived from toasted wood [ 66 ].…”
Section: The Influence Of Wood On the Quality Of Alcoholic Beveragesmentioning
confidence: 99%
“…Nevertheless, the quantities thus formed cannot rival the levels released by some types of oak wood during wine aging [ 16 ]. Therefore, the quantification of vanillin derivatives is essential in red or white wines aged with oak chips or oak barrels [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%